ELABORACIÓN DE UN ENVASE BIODEGRADABLE A PARTIR DE RESIDUOS DE CORTEZA DE CACAO (Theobroma cacao) Y CASCARILLA DE ARROZ (Oryza sativa) - Bolaños Suárez , Wendy Janeth (2023)
A biodegradable container is one made with organic matter that, when discarded or in contact with the environment, tends to decompose more easily and quickly, turning into biomass and nutrients, unlike plastic containers. This research was carried out at the Quevedo State Technical University, Los Ríos province. It is the result of an experimental, bibliographical and analytical study, which is oriented towards the development of a tray-type biodegradable container through the use of residues of cocoa bark (Theobroma cacao) and rice husks (Oryza sativa), therefore which the established objectives have the purpose of a physical chemical evaluation (moisture content, ash and thickness) of the biodegradable container and the determination of production performance. For the execution of this investigation, an AxB factorial design was proposed using six treatments with three replicates, these being the mixtures of the particles (cocoa bark and rice husk) with the type of binder (CMC and Cornstarch). According to obtaining the results, in the moisture content treatment 1 with 8.9% in (a0b0) (30% cocoa husk + 70% rice husk + CMC) obtained the best result, in ashes 0.11% obtained the best result. Best result treatment 6 (70% cocoa shell + 30% rice husk + cornstarch) and according to the thickness parameter treatment 1 (30% cocoa shell + 70% rice husk + CMC) with a 0.43 x 1.18 cm. Based on the yield of the product, 50.71% was obtained, obtaining loss in the drying process. In conclusion, it was determined that the best treatment was treatment 1 (a0b0) (30% cocoa husk + 70% rice husk + CMC), because it obtained good physical-chemical parameters and better raw material yield.